Exploring Vietnamese Students’ Participation and Perceptions of Science Classroom Environment in STEM Education Context - Ngan, Le Hai My; Hien, Nguyen Van; Hoang, Le Huy; Hai, Nguyen Duy; Bien, Nguyen Van (Jurnal Penelitian dan Pembelajaran IPA, 2020)
One of the concerns for applying STEM education in the classroom is students’ participation. In this study, the Engagement and Participation in Classroom – Science (EPIC-S) questionnaire was applied to explore Vietnamese students’ participation behaviors and their perceptions of the science classroom environment. The main goal of our study was to investigate the impact of students’ classroom participation on their perceptions of the science classroom environment as assessed by the EPIC-S questionnaire. Our survey was conducted on 884 students in some public secondary schools in Vietnam and the collected data was analyzed using SPSS 20. Students were classified into two groups-verbal and silent- based on how they participated in several facets of the science classroom environment. We found no statistically significant difference between these two groups in their perception of the relationship with the teacher. Nevertheless, there are differences in their perceptions of peer support, fear of embarrassment, and teacher openness. Our results will contribute to the theoretical background for STEM education in Vietnam